Spine biomechanics associated with the shortened, modern one-plane golf swing - Dale, R. B.; Brumitt, J. (Sports Biomechanics, 2016)
The purpose of this study was to compare kinetic, kinematic, and performance variables associated with full and shortened modern backswings in a skilled group of modern swing (one-plane) golfers. Shortening the modern golf backswing is proposed to reduce vertebral spine stress, but supporting evidence is lacking and performance implications are unknown. Thirteen male golfers performed ten swings of each swing type using their own 7-iron club. Biomechanical-dependent variables included the X-Factor kinematic data and spine kinetics. Performance-related dependent variables included club head velocity (CHV), shot distance, and accuracy (distance from the target line). Data were analysed with repeated measures ANOVA with an a priori alpha of 0.05 (SPSS 22.0, IBM, Armonk, NY, USA). We found significant reductions for the X-Factor (p<0.05) between the full and shortened swings. The shortened swing condition ameliorated vertebral compression force from 7.6±1.4 to 7.0±1.7N (normalised to body weight, p=0.01) and significantly reduced CHV (p< 0.05) by ~2m/s with concomitant shot distance diminution by ~10m (p<0.05). Further research is necessary to examine the applicability of a shortened swing for golfers with low back pain.